The development of the 5Cs of positive youth development in a school year: A 3-wave longitudinal study of Slovenian youth during the COVID-19 pandemic - Kozina, Ana; Wiium, Nora (Frontiers in Psychology, 2023)
The paper analyses the longitudinal pathways for the 5Cs of positive youth development outcomes (Competence, Confidence, Character, Caring, Connection) in a school context during the COVID-19 pandemic. The theoretical framework for the paper is provided by the Positive youth development (PYD) perspective, which focuses on the importance of the interplay between individual characteristics and contexts. In the period of adolescence, school and its characteristics are one of the most influential contexts for the promotion of positive youth development. Therefore, the paper focused on the changes in the 5Cs in one school year using the methodology of longitudinal research (latent growth modeling) with three measurement points (beginning of the school year, middle of the school year, and the end of the school year). We used a sample of Slovenian youth (N = 1241 participants; 59,5 % female; Mage = 15.35, SD = 1.21) who participated in the PYD-SI-MODEL study and responded to the PYD questionnaire (Geldhof et al., 2014) during the current COVID-19 pandemic. In addition, we tested whether the development of the 5Cs in a school year differed by gender, age, and school level (lower-secondary, upper-secondary). The results indicated a significant decrease in Connection, Caring, and Character from the beginning to the end of the school year and an increase in Competence and Confidence in the same period. Significant intercept-slope interactions were detected in Confidence and Connection indicating that their higher initial level is associated with a more stable trajectory throughout the school year. In addition, we found that gender and school level play a significant role in several of the pathways while age was not a significant covariate with any of the Cs. The study is the first to test 5Cs pathways in one school year, using Slovenian data. In addition to the important role of contexts on positive developmental outcomes, the study highlights the significance of 5Cs promotion in pandemic times as much as in more stable times.